Analisis SWOT untuk Strategi Pengembangan Objek Wisata Hutan Bakau Kormun Wasidori Arfai di Manokwari - Dedy Riantoro; Jhon Aninam (Lensa Ekonomi, 2021)
This study aims to find a strategy for developing a tourism object for the Kormun Wasidori Mangrove Forest which is located in Arfai, South Manokwari District, Manokwari Regency. The research was conducted to identify internal and external factors which were then scored and analyzed, then a strategy was formulated for development by minimizing weaknesses and threats and maximizing the utilization of opportunities and strengths. Data were collected through the distribution of questionnaires, documentation, and field interviews with informants from owners or managers, surrounding communities, and visitors to tourism objects. Data were analyzed using SWOT analysis. Strength factors are: strategic location, original, beautiful and cool natural panorama, unique and natural natural attractions, and a fairly cheap price. Weakness factors are: lack of cooperation with local governments, and low public awareness of protecting the environment. Opportunity factors are: the potential for mangrove conservation, and the absorption of local labor that can reduce unemployment. Threat factors are: the potential for environmental or coastal pollution, and the lack of attention from the government. The development strategy is: cooperation with local governments to jointly manage and develop this tourism object, increase community participation, use local labor in the management of this tourism object, and utilize the potential of the local tourism market segment to increase the number of tourists visiting tourism objects Kormun Wasidori Arfai Mangrove Forest. This is done by means of promotion. Penelitian ini bertujuan untuk mengetahui strategi pengembangan objek wisata Hutan Mangrove Kormun Wasidori yang terletak di Arfai, Kecamatan Manokwari Selatan, Kabupaten Manokwari. Penelitian dilakukan untuk mengidentifikasi faktor internal dan eksternal yang kemudian dinilai dan dianalisis, kemudian dirumuskan strategi pengembangan dengan meminimalkan kelemahan dan ancaman serta memaksimalkan pemanfaatan peluang dan kekuatan. Pengumpulan data dilakukan melalui penyebaran angket, dokumentasi, dan wawancara lapangan dengan informan dari pemilik atau pengelola, masyarakat sekitar, dan pengunjung objek wisata. Analisis data menggunakan analisis SWOT. Faktor kekuatan adalah: lokasi strategis, asli, panorama alam yang indah dan sejuk, wisata alam yang unik dan alami, serta harga yang cukup murah. Faktor kelemahannya adalah: kurangnya kerjasama dengan pemerintah daerah, dan rendahnya kesadaran masyarakat untuk menjaga lingkungan. Faktor peluang yaitu: potensi konservasi mangrove, dan penyerapan tenaga kerja lokal yang dapat mengurangi pengangguran. Faktor ancaman adalah: potensi pencemaran lingkungan atau pesisir, dan kurangnya perhatian dari pemerintah. Strategi pengembangannya adalah: kerjasama dengan pemerintah daerah untuk bersama-sama mengelola dan mengembangkan objek wisata ini, meningkatkan partisipasi masyarakat, menggunakan tenaga kerja lokal dalam pengelolaan objek wisata ini, dan memanfaatkan potensi segmen pasar pariwisata lokal untuk meningkatkan jumlah kunjungan wisatawan. Obyek Wisata Hutan Mangrove Kormun Wasidori Arfai. Hal ini dilakukan dengan cara promosi.